Study association of urinary Club Cell Protein with air pollution-related pulmonary function compromised among children - Avinash Pagdhune; Ankit Sheth; Sarang Dhatrak; Ankit Viramgami (Clinical Epidemiology and Global Health, 2024)
Background: Childhood exposure to air pollution exacerbates respiratory conditions and even carries deleterious effects on lung functions in adulthood. It is desirable to establish a non-invasive screening test for children to predict early lung insult with air pollution exposure. The association between serum club cell protein (CC16) and obstructive airway diseases is known, but the same is not explored with air-pollution-related lung insult and pulmonary function test (PFT) parameters. Aim: To investigate the association between urinary CC16 and PFT parameters in children exposed to differing levels of air pollution. Methods: This cross-sectional study recruited 107 children from critically-polluted area (CPA) and 96 age-sex-matched children from non-polluted area (NPA). PFT and urinary CC16 were determined with standard techniques. Air quality parameters were estimated with adherence to National Ambient Air Quality Standards (NAAQS). Results: CPA was observed with 2.5 times poorer Air-Quality-Index compared to NPA. Urinary CC16 levels of children were four-fold higher in CPA compared to NPA (p < 0.001). CPA children were significantly deprived in PFT parameters [FVC(L)-1.86 v/s 2.02, p = 0.01; FEV1(L/s)-1.71 v/s 1.86, p = 0.01 & PEFR(L/s)- 3.25 v/s 3.69, p < 0.001]. While adjusted for physiological parameters, urinary CC16 observed with significant negative association with PFT parameters (FVC: β = −0.02, p=0.03; FEV1: β = −0.03, p=0.001 & FEF25–75 %: β = −0.05, p=0.04). Conclusion: The significant decline in lung function parameters and elevated urinary CC16 levels among children in polluted areas underscore the need for further research to validate urinary CC16 as a reliable screening tool for respiratory health monitoring among children.